2013
DOI: 10.1080/10963758.2013.777587
|View full text |Cite
|
Sign up to set email alerts
|

A Survey of Doctoral Theses Accepted by Universities in the United Kingdom and Ireland for Studies Related to Tourism, 2000–2009

Abstract: demonstrating the previous work related to tourism postgraduate studies to identify trends and disclose associated issues. Subsequently, the research illustrates the methodological approach utilized before providing an analysis of both chronological and geographical distributions of tourism PhD theses awarded in the United Kingdom and Ireland. The research also sheds light as well on the most attractive and relatively neglected areas of tourism PhDs, which might be of a special importance for universities work… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0
3

Year Published

2014
2014
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 25 publications
0
6
0
3
Order By: Relevance
“…Akár tudományként, akár ismeretterületként tekintünk magára a turizmusra, a kutatóműhelyekben, kitüntetetten a tudományos utánpótlás-neveléssel foglalkozó doktori iskolákban elkészített PhD-értekezések elfogadásának legfőbb kritériuma az új vagy újszerű tudományos eredmények megléte és azok érvényességének alátámasztása (Pearce, 2005). A turisztikai tudás sajátosságainak doktori értekezésekben való megjelenését Jafari és Aaser (1988) már több mint három évtizede vizsgálta és a munkásságukat követő szerzők (Bao, 2002;Meyer-Arendt & Justice, 2002;Afifi, 2009Afifi, , 2013Huang, 2011;Weiler et al, 2012) az ő metodikai nyomdokaikon folytatták a turizmus tudományosítását megtestesítő dolgozatok értékelését. Jafari és Aaser (1988) amerikai és kanadai egyetemeken 1951 és 1986 között elkészített 157 darab, turizmusfókuszú doktori értekezés alapján megállapította, hogy a sporadikus kezdet után a '70-es, '80-as években folyamatosan növekedett az ilyen témájú munkák előfordulása, amelyek leginkább közgazdasági, antropológiai, földrajzi és rekreológiai színezetűek voltak.…”
Section: Elméleti Háttérunclassified
See 1 more Smart Citation
“…Akár tudományként, akár ismeretterületként tekintünk magára a turizmusra, a kutatóműhelyekben, kitüntetetten a tudományos utánpótlás-neveléssel foglalkozó doktori iskolákban elkészített PhD-értekezések elfogadásának legfőbb kritériuma az új vagy újszerű tudományos eredmények megléte és azok érvényességének alátámasztása (Pearce, 2005). A turisztikai tudás sajátosságainak doktori értekezésekben való megjelenését Jafari és Aaser (1988) már több mint három évtizede vizsgálta és a munkásságukat követő szerzők (Bao, 2002;Meyer-Arendt & Justice, 2002;Afifi, 2009Afifi, , 2013Huang, 2011;Weiler et al, 2012) az ő metodikai nyomdokaikon folytatták a turizmus tudományosítását megtestesítő dolgozatok értékelését. Jafari és Aaser (1988) amerikai és kanadai egyetemeken 1951 és 1986 között elkészített 157 darab, turizmusfókuszú doktori értekezés alapján megállapította, hogy a sporadikus kezdet után a '70-es, '80-as években folyamatosan növekedett az ilyen témájú munkák előfordulása, amelyek leginkább közgazdasági, antropológiai, földrajzi és rekreológiai színezetűek voltak.…”
Section: Elméleti Háttérunclassified
“…Weiler et al (2012) szélesebb angolszász perspektívában (USA, Kanada, Ausztrália és Új-Zéland) végzett, időben is kiterjedtebb (1951-2010) kutatása megerősítette az exponenciális növekedés tényét, ugyanakkor rámutatott a gazdaságtudományi megközelítések visszaszorulására, továbbá új és újabb tudományok (például pszichológia, környezettudományok) előretörésére. Hasonló eredményre jutottak a legkülönbözőbb földrajzi relációban készített vizsgálatok, így Afifi (2009) egyiptomi kötődésű, illetve az Egyesült Királyságra és Írországra fókuszáló munkája (Afifi, 2013) és Huang (2011) kínai helyzetfeltáró elemzése. Bao (2002) Kínában végzett, kifejezetten a turizmusföldrajzra koncentráló kutatása megállapította, hogy ezen a szakterületen 1989-ben született meg az első doktori értekezés, amely -a nemzetközi előzményekhez hasonlóan -exponenciális növekedést indukált, a világ turizmusának élvonalába is felzárkózó országban a Kínai Tudományos Akadémián készítették a legtöbb turizmusföldrajzi tárgyú PhD-disszertációt.…”
Section: Elméleti Háttérunclassified
“…In particular, theses aligned with the event studies field generated by researchers from various Australian universities over the period 1995-2015 provide the sample for the current study. Following a tradition of such studies in the tourism field (Afifi, 2013;Meyer-Arendt & Justice, 2002;Weiler, Moyle, & McLennan, 2012), the abstract data accompanying each thesis is content analyzed to scope out the disciplinary lens used by the next generation of event studies researchers to elucidate new knowledge in the field. Gaps and opportunities for further development will be identified.…”
Section: Lockstone-binneymentioning
confidence: 99%
“…Indeed, Afifi (2013) noted the rise of Ph.D. students in the UK from "pure tourism backgrounds" (p. 30) as opposed to earlier years (in particular the mid-1960s) when students generally came from established disciplines. A number of these studies highlight the explosion of tourism theses in recent years (Afifi, 2013;Huang, 2011;Meyer-Arendt & Justice, 2002), which Botterill et al (2002) suggested is evidence of the status of tourism as a distinct field of study in its own right. Additionally, there is evidence that the disciplines informing tourism theses are growing in scope and variety (Meyer-Arendt & Justice, 2002;Weiler et al, 2012).…”
Section: Literature Reviewmentioning
confidence: 99%
“…This job also gives candidates and supervisors some information about which subjects have been popular while which have not been considered. Some studies have been done which were investigated subject contents of the tourism PhD dissertations in different countries like Australia (Hall, 1991), North America (Meyer-Arendt and Justice, 2002), the UK and Ireland (Botterill, Haven and Gale, 2002), France and Spain (Martinez and Herraez, 2004), Brasil (Santos et al 2009), China (Huang, 2011), Egypt (Afifi, 2009) and the UK and Ireland (Afifi, 2013). However, none of these study were focused on examine the hospitality area.…”
Section: Introductionmentioning
confidence: 99%